Produksi Film Pendek â€œLike And Dislike â€ Menggunakan Sistem Multimedia - Utomo, Pandu; Purnama, Bambang Eka; Urbani, Yunan Hepy (APMMI - Asosiasi Profesi Multimedia Indonesia)
Abstract - Development of the University of Surakarta assessed memorable film monotonous, it does not result in the development of cinema that puts the educational aspect. Short Film Production